Multiple factors affecting Ixodes ricinus ticks and associated pathogens in European temperate ecosystems (northeastern France) - Nathalie Boulanger; Delphine Aran; Armand Maul; Baba Issa Camara; Cathy Barthel; Marie Zaffino; Marie-Claire Lett; Annick Schnitzler; Pascale Bauda (Scientific Reports)
Abstract In Europe, the main vector of tick-borne zoonoses is Ixodes ricinus, which has three life stages. During their development cycle, ticks take three separate blood meals from a wide variety of vertebrate hosts, during which they can acquire and transmit human pathogens such as Borrelia burgdorferi sensu lato, the causative agent of Lyme borreliosis. In this study conducted in Northeastern France, we studied the importance of soil type, land use, forest stand type, and temporal dynamics on the abundance of ticks and their associated pathogens. Negative binomial regression modeling of the results indicated that limestone-based soils were more favorable to ticks than sandstone-based soils. The highest tick abundance was observed in forests, particularly among coniferous and mixed stands. We identified an effect of habitat time dynamics in forests and in wetlands: recent forests and current wetlands supported more ticks than stable forests and former wetlands, respectively. We observed a close association between tick abundance and the abundance of Cervidae, Leporidae, and birds. The tick-borne pathogens responsible for Lyme borreliosis, anaplasmosis, and hard tick relapsing fever showed specific habitat preferences and associations with specific animal families. Machine learning algorithms identified soil related variables as the best predictors of tick and pathogen abundance.